A prática pedagógica da professora de piano : Irmã Augusta da Costa Marques (1979-2000) - Dias, Luis Renato dos Santos (2021)
This dissertation presents a research project completed as part of the Graduate Level program in Education at the Federal University of Mato Grosso (UFMT). Specifically, it was completed under the Group for Historical Research in Education and Memory (GEM). The objective of the research was to analyse the educational practices used by Salesian Sister Augusta Costa Marques in her career as a piano teacher, thus delineating her contribution to musical education in Guiratinga, Mato Grosso (MT), where she lived and taught for two decades. The research indicated that since 1894 the Santa Rita Home, a religious school for girls in Cuiaba, MT, offered piano lessons. Under the leadership of the “Blue Sisters”, the Home’s staff included Sister Marie Vicent and the Salesian Sister Alzira Bastos, who was the piano teacher of a young Augusta Costa Marques. The research project was carried out by the gathering and organizing of various documents, specifically: 1) a Dossier and Memorial of Sister Augusta Costa Marques; 2) the Religious Chronicles of the Santa Terezinha School; 3) an assignment book of a former student; 4) a book of poetry written by Sister Augusta Costa Marques; and an assortment of letters, books and printed piano music. The dissertation represents the years from 1979 to 2000. In order to attain the delineated objectives, the concept of The Evidential Paradigm taught by Carlo Ginzburg (1989) was utilized as a theoretical and methodological standard. Other concepts applied include that of Cultural Development taught by Norbert Elias (2011), and Principles of Private Piano Teaching by Adriana Bozzeto (2004). The conclusions drawn indicate that Sister Augusta Costa Marques, in her religious and educational roles, applied what she had learned of music with her knowledge of teaching reading which she learned in teacher training school,and adapted these principles to her piano teaching. The fusion of these two areas of knowledge served well as a basis for teaching music from a culltural perspective in which she taught her students correct etiquette for a piano player.